Field activities within an environmental sciences program: a b-learning case study - Caeiro, Sandra (2021)
A reflection on the use of fieldwork in environmental science programmes is conducted in this paper. It is generally agreed that for fieldwork to be effective, it must serve a clear purpose in the curriculum. For a good curriculum design, a fieldwork course must complement, enhance or extend an existing part of the curriculum or fulfil some major objective of the curriculum as a whole. Thus a successful integration of fieldwork within an undergraduate degree programme is particularly important. For an environmental science course delivered through online methodology, it becomes evident that special attention should be devoted to the design and implementation of such a course. If we consider the more general definition where the field is seen as the location, outside the classroom setting, where learning takes place, then fieldwork is the set of activities that will facilitate students’ learning. It is generally agreed that a field course is much more difficult to integrate than a set of activities closely related to a specific subject. However, in a distance-learning university it is not plausible that students perform this type of activity very often. Therefore, the field courses are designed as a stand-alone module. The current work analyzes the design of the course entitled Fieldwork II which is integrated in the undergraduate degree in Environmental Sciences at Universidade Aberta. Many issues have to be taken into account when designing such a course that encompasses legislative, pedagogical and logistical matters. An overview of the research work that has been developed on the pedagogical value of fieldwork is given. Taking into account the specific learning methodology adopted at Universidade Aberta, we also present a fieldwork model for environmental sciences in a context of a blended learning (b-learning) undergraduate programme. The organizational effectiveness of the model and students’ participation was assessed in two scholar years of a fieldwork course at Universidade Aberta. Also, the project assignment synopses were assessed in the context of education for sustainability. Finally, it should be stressed that fieldwork should be regarded as a form of learning which exploits the unique characteristics of the field environment to improve the student learning experience.